Psychological predictors of perceived quality of life among people living with HIV and AIDS in South West Nigeria (2013)
This study examined the dynamics of perceived social support and self-esteem in predicting perception of quality of life among People Living with HIV/AIDS (PLWHA) in South West Nigeria. One hundred and fifty nine (159) PLWHA selected using the purposive sampling technique participated in the study; the sample was made up of 46 males and 113females, aged between 19 and 72 years. Data were collected using a structured questionnaire. The result of the multiple regression analysis showed that perceived social support and self-esteem significantly jointly predicted perceived quality of life among PLWHA (p< .05). Self-esteem significantly independently predicted perceived quality of life(p< .05) while perceived social support did not significantly predict perceived quality of life. A t-test indicated no gender differences in perception of quality of life. The study therefore concluded that psychological interventions are required to shore-up the self-esteem of PLWHA alongside social support to enable them to cope better and be more optimistic and positive in their perception of quality of life